Commercialization channels of organic products in Brazil: Analysis at the first level of the production chain - Scalco, Andréa Rossi [UNESP]; Pigatto, Giuliana Aparecida Santini [UNESP]; Souza, Roberta (FapUNIFESP (SciELO), 2017)
Specialized literature on organic production highlights the presence and concentration of retail, especially supermarkets, in the organic enhancement chain. This presents enormous obstacles for the entrance of small farmers in the production of organic products due to administrative barriers, in addition to pressure for lower prices by the supermarket retail network. This paper investigates the commercialization channels of organic production in Brazil. The survey was undertaken in 2013; questionnaires were sent to 900 out of approximately 11.200 farmers producing organic products; 216 answers were received. Analysis showed that approximately 90% of farmers provided for the internal market and 60% of the products were fresh fruits and vegetables. The distribution of organic products in Brazil is highly fragmented at the local, regional and national levels. The presence of supermarkets and intermediaries in the commercialization of fruits and vegetables is relevant, regardless of the size of the farm. There is a great dispersion of channels in the case of small farmers, although supermarkets rank second. However, direct commercialization (farmers markets) is the main form of commercialization of the produce. Commercialization triggered by social programs has guaranteed a considerable part of the income on small production units or small farms. It seems that high involvement of retail networks and agents in the agribusiness segment causes low development rates in small agricultural units and in local development due to the latter's low profit margins.
Keywords: Commercialization channels; Organic farmers; Organic products